Renal Dose Dopamine Mediates the Level of Aquaporin-2 Water Channel (Aqp2) in Broiler Chickens - Chang,Z (2017)
ABSTRACT Aquaporin 2 (AQP2) is a small protein located in the collecting tubules of kidneys; it plays an important role in the concentration and production of urine. The aim of this study was to determine the expression level of the AQP2 gene in the kidney of broiler chickens after the administration of renaldose dopamine. Broiler chickens (25 days-old) were randomly divided into two groups (n=20 per group): intravenous administration of saline solution (control group) or renal-dose dopamine (dopamine group). The expression and localization of the AQP2 gene were evaluated by real-time quantitative polymerase chain reaction (RT-qPCR) and immunohistochemistry (IHC), respectively. The protein level of AQP2 was analyzed by western blot analysis. The dopamine group presented no significant difference (p>0.05) in the biochemical criterion or mRNA expression of AQP2 compared with the control group. However, AQP2 protein level was significantly reduced (p<0.05) in the membrane of renal tubular epithelial cells. In contrast, protein level was significantly increased (p<0.05) in the cytoplasm of the dopamine group compared with the control group. Moreover, AQP2 protein was apparently more distributed and localized in the cytoplasmic vacuoles than in the membranes of the kidney in the renaldose dopamine administered chickens group. In conclusion, present findings suggest that renaldose dopamine mediates the level of AQP2 protein via shuttle from the cell membrane to the cytoplasm rather than changing the expression of AQP2 gene to adjust the secretion and absorption of water in kidney.